An Assessment of Fuel from Disposed Plastic Containers for Diesel Engine - Gupta, A. D.; Gupta, Ashish; Seema; Varshney, L. (International Journal of Bio-resource and Stress Management, 2019)
The present work is focused on the methodology for production of alternative fuel for automobile engines along with waste material management. This is done using pyralysis, which is a technique used to produce liquid fuel from solid waste material using a reactor unit. In the present investigation, an electrically operated pyrolysis reactor unit with thermostat (a temperature control device) with water-cooled condenser is used for the pyrolysis process. An attempt is made to obtain the pyrolysis oil from the waste plastic bottles disposed of after use. Used plastic bottles are collected from various places like railway station, restaurants and other places where disposable water bottles and other plastic containers are thrown away. These plastic bottles and containers are initially washed for removing impurities and then dried in the open air for about two days. In the experimental process, 2.5 kg of crushed bottles are taken and using pyrolysis reactor unit these are converted into oil. Brown colored oil produces after the process is collected. Various ignition properties of the pyrolysis oil obtained are evaluated and analyzed. Important characteristics of the fuel obtained from the pyrolysis process are compared with the high-speed diesel. It is observed that the obtained pyrolysis oil has properties similar to the high-speed diesel. Experimental investigation reveal that ignition properties of the pyrolysis oil are suitable for use in diesels engine with minor design modifications.